Isotopic characterization of vanillin ex glucose by GC-IRMS - New challenge for natural vanilla flavour authentication?. (December 2019) - Wilde, Amelie S.; Frandsen, Henrik Lauritz; Fromberg, Arvid; Smedsgaard, Jørn; Greule, Markus
Abstract: Vanilla flavour is highly vulnerable to economically motivated adulteration as the main component vanillin can be derived by much cheaper production methods than by the extraction from vanilla pods. The δ 13 C ranges for synthetic vanillin from petroleum and C3 plants are depleted in comparison to the reported δ 13 C range for vanillin from vanilla orchids. However, with the invention of new biosynthetic pathways, vanillin overlapping with the characteristic δ 13 C range reported for vanillin from vanilla pods can be produced. Here, we present bulk and site-specific analysis by GC-IRMS of stable carbon and hydrogen isotope ratios of vanillin derived from glucose. This is the first time a δ 13 C value for biovanillin that is higher compared to vanillin from vanilla pods is reported. The possibility to simulate the δ 13 C range of vanillin from vanilla pods by combining vanillin derived from inexpensive sources constitutes an increased risk for fraud being perpetrated while remaining unnoticed. Highlights: Carbon and hydrogen isotopic ratio characterisation of vanillin ex glucose. Database extension of vanilla pods originating from 16 different countries. Carbon and hydrogen isotopic ratio characterisation of a vanilla hybrid.